The Captive Mind In Development Studies. [Part 1] - Alatas, Syed Hussein (1972)
In The Annals of The American Academy of Political and Social Science, November 1966,. appeared an •article entitled 'The Professor Abroad'. The author, Edward W. Weidner, himself a professor of political science, is an experienced and well..qualified person to speak about the effect and• function of the American professors abroad.